Multiplex PCR and Microarray for Detection of Swine Respiratory Pathogens. Issue 3 (12th December 2015) - Lung, O.; Ohene‐Adjei, S.; Buchanan, C.; Joseph, T.; King, R.; Erickson, A.; Detmer, S.; Ambagala, A.
Summary: Porcine respiratory disease complex (PRDC) is one of the most important health concerns for pig producers and can involve multiple viral and bacterial pathogens. No simple, single‐reaction diagnostic test currently exists for the simultaneous detection of major pathogens commonly associated with PRDC. Furthermore, the detection of most of the bacterial pathogens implicated in PRDC currently requires time‐consuming culture‐based methods that can take several days to obtain results. In this study, a novel prototype automated microarray that integrates and automates all steps of post‐PCR microarray processing for the simultaneous detection and typing of eight bacteria and viruses commonly associated with PRDC is described along with associated multiplex reverse transcriptase PCR. The user‐friendly assay detected and differentiated between four viruses [porcine reproductive and respiratory syndrome virus (PRRSV), influenza A virus, porcine circovirus type 2, porcine respiratory corona virus], four bacteria ( Mycoplasma hyopneumoniae, Pasteurella multocida, Salmonella enterica serovar Choleraesuis, Streptococcus suis ), and further differentiated between type 1 and type 2 PRRSV as well as toxigenic and non‐toxigenic P. multocida . The assay accurately identified and typed a panel of 34 strains representing the eight targeted pathogens and was negative when tested with 34 relevant and/or closely related non‐target bacterial and viral species. All targets were also identified singly or in combination in a panel of clinical lung samples and/or experimentally inoculated biological material.